Do financial bonuses to employees reduce their absenteeism? Outcome of a lottery - Wolter H.J. Hassink; Pierre Koning (Institute for the Study of Labor (IZA), 2005)
This paper investigates the effectiveness of a monthly lottery in reducing sick leave among workers in a manufacturing firm. Conditions of participation are not having reported sick in the previous three months and not having won the lottery earlier. It turns out that the lottery results in a decrease in the rate of sick leave of 1.6 percentage point. From the perspective of the firm, the lottery is found to be highly beneficial that is, the benefits associated with the decrease in the sick leave rate exceed the costs of the lottery. Workers seem to be primarily driven by the first upcoming lottery. After winning the lottery, winners resume their previous (rate of) absence.
Keywords: J22; J32; M52; 330; absenteeism; sick leave; incentives; lottery; Leistungsorientierte Vergütung; Fehlzeit; Glücksspiel; Niederlande